Phototherapy and mycosis fungoides: what’s new? (Dermatology Reports, 2023)
The most common cutaneous T-cell lymphoma, mycosis fungoides (MF), is clinically characterized by erythematous-violaceous nodules and erythematous-scaly patches. In the early stages of MF, phototherapy is currently the first line of treatment and plays a significant role. This study aims to review and analyze the various phototherapy options for cutaneous lymphoma.